PENERAPAN BANTUAN HUKUM DI INDONESIA - Siregar, Friska Anggi (State of Islamic Institute Langsa, 2018)
law (rechtsstaat) recognizes and protects human rights. All people must be treated equally in the law. Equality in law must be balanced with equal treatment. Legal assistance is the right of a person who is involved in a criminal case to be able to prepare a defense or counseling in upholding his rights as a suspect. Everyone has the right to receive legal assistance from an advocate, no one may be denied the right to obtain a legal defense in a legal state. Provision of legal assistance does not look at religious, ancestral, racial, ethnic, political beliefs, socio-economic strata, skin color and gender. Thus, justice will be realized for everyone